Traditional Knowledge In Practice - Abele, Frances (ARCTIC, 1997)
Northern organizations, governments, and governments-in-waiting have been formally and informally attempting to incorporate "traditional knowledge" into policy deliberations for some time. A public debate about this practice began in fall 1996, when Frances Widdowson and Albert Howard published criticisms of the Government of the Northwest Territories" (GNWT) Traditional Knowledge Policy and of the requirement that traditional knowledge be incorporated into environmental assessments. Widdowson was at the time a contract employee of the Department of Resources, Wildlife and Economic Development (Howard and Widdowson, 1996). As the controversy developed, she was suspended for one week as punishment for her public criticism of government policy. In the Canadian parliamentary tradition, public servants do not have the right to publicly disagree with the policies they are hired to implement. Employees who find themselves in fundamental disagreement with the decisions of elected officials have two options: they may work from within to bring about a change of policy; or, failing this, they must resign. As private citizens, they may - and should - criticize government policy freely. Widdowson should have resigned before speaking publicly, but at least her action stimulated public discussion of some very important questions (GNWT, 1993; Howard and Widdowson, 1996; Berkes and Henley, 1997; Howard and Widdowson, 1997; Laghi, 1997; Stevenson, 1997). The GNWT has adopted what is probably the first formal traditional knowledge policy in Canada, in an attempt to improve democratic representation in the North by moving the policies and practices of territorial government closer to reflecting the values and needs of all northern residents. The Traditional Knowledge Policy is only one aspect of this endeavour, but it is a potentially far-reaching one that deserves intelligent discussion and debate. .